2021
DOI: 10.2196/30919
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Supermarket Program for the Screening of Mild Cognitive Impairment in Older Adults: Diagnostic Accuracy Study

Abstract: Background Mild cognitive impairment (MCI) is often a precursor of dementia, and patients with MCI develop dementia at a higher rate than healthy older adults. Early detection of cognitive decline at the MCI stage supports better planning of care and interventions. At present, the use of virtual reality (VR) in screening for MCI in older adults is promising, but there is little evidence regarding the use of virtual supermarkets to screen for MCI. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Two types of tasks for yielding digital biomarkers were identified: one is active tasks that require active engagement in the evaluation, such as computerized versions of traditional cognitive tests (e.g., [ 15 , 16 ]) or online games (e.g., [ 17 , 18 , 19 ]) for assessing a broad domain of cognitive functions, voluntary speech production for assessing language ability [ 20 ], or virtual reality techniques (e.g., [ 21 , 22 ]). Another type is passive tasks in which people were monitored without active input, such sleep quality, walking speed, phone usage, and daily activities [ 13 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two types of tasks for yielding digital biomarkers were identified: one is active tasks that require active engagement in the evaluation, such as computerized versions of traditional cognitive tests (e.g., [ 15 , 16 ]) or online games (e.g., [ 17 , 18 , 19 ]) for assessing a broad domain of cognitive functions, voluntary speech production for assessing language ability [ 20 ], or virtual reality techniques (e.g., [ 21 , 22 ]). Another type is passive tasks in which people were monitored without active input, such sleep quality, walking speed, phone usage, and daily activities [ 13 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 55 studies ( Fujiwara et al, 2010 ; Lu et al, 2011 ; Ahmed et al, 2012 ; Larner, 2012 ; Yu et al, 2012 ; Dong et al, 2013 ; Freitas et al, 2013 ; Memória et al, 2013 ; Roalf et al, 2013 ; Cummings-Vaughn et al, 2014 ; Goldstein et al, 2014 ; Kaya et al, 2014 ; Malek-Ahmadi et al, 2014 ; Yeung et al, 2014 ; Zhou et al, 2014 ; Chu et al, 2015 ; Julayanont et al, 2015 ; Ng et al, 2015 ; Trzepacz et al, 2015 ; Mellor et al, 2016 ; O’Caoimh et al, 2016 ; Tsai et al, 2016 ; Cecato et al, 2017 ; Clarnette et al, 2017 ; Janelidze et al, 2017 ; Bartos and Fayette, 2018 ; Chiu et al, 2018 ; Lee et al, 2018 ; Li et al, 2018 ; Cesar et al, 2019 ; Delgado et al, 2019 ; Rossetti et al, 2019 ; Townley et al, 2019 ; Wang et al, 2019 ; Pinto et al, 2019b ; Aycicek et al, 2020 ; Bello-Lepe et al, 2020 ; Dautzenberg et al, 2020 ; Freud et al, 2020 ; Senda et al, 2020 ; Serrano et al, 2020 ; Sokołowska et al, 2020 ; Thomann et al, 2020 ; González et al, 2021 ; Hemrungrojn et al, 2021 ; Masika et al, 2021 ; Rashedi et al, 2021 ; Rodríguez-Salgado et al, 2021 ; Yan et al, 2021 ; Pan et al, 2022 ; Paterson et al, 2022 ) were included in this meta-analysis from which 40 were used in the AUC analysis and 45 were used in the analysis of mean differences. Thirty-one of the included studies were used in both the AUC and mean difference analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The two significant barriers identified in the above-mentioned study by providers were cognitive issues displayed by the patient and patient’s perceptions of technology. Even though cognitive impairment can serve as a hinderance for engagement in some VR activities, VR has also acted as an assessment tool for diagnosing mild cognitive impairment [ 26 ]. Researchers have found that VR applications can be used toward improvement of cognitive impairment [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%